Sexual Violence on Public Transportation: A Threat to Women's Mobility in Bangladesh. Issue 8 (14th September 2019) - Mazumder, Hoimonty; Pokharel, Bishant
ABSTRACT: Recent violence against women has been turned into a different approach in the urban cities, representing extreme intimidation towards women's freedom of mobility and dignity. Sexual violence in public transport is one of such violence that is extremely invisible in the society due to high rates of under-reporting, so nationally this issue has not been acknowledged yet in Bangladesh. Therefore, a consequence of this violence not only confined women's life but also created a hostile environment towards empowerment.